PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN GOOGLE WORKSPACE TERHADAP KETERAMPILAN KOMUNIKASI SISWA DALAM PEMBELAJARAN BIOLOGI SELAMA PANDEMI - Adawiyah, Marosa Robi’atul (Jurnal al Muta'aliyah: Pendidikan Guru Madrasah Ibtidaiyah, 2022)
Abstract The purpose of this study was to determine differences in the communication skills of students who underwent learning using the Problem-Based Learning model assisted by Google Workspace and regular learning. Google Workspace is a tool in the form of an application that is used as an aid to facilitate online learning during a pandemic, the applications used include Google Classroom, Google Documents, Google Forms and Google Meet. This study used a quantitative approach with a quasi-experimental method with a nonequivalent control group design. The sample in the study were students of class XI IPA 3 (experimental class) and XI IPA 4 (control class) at SMA Lab Malang, where the experimental class was taught using the PBL learning model with Google Workspace and the control class was taught by regular learning. Communication skills are measured using observation sheets that have been adapted to indicators of communication skills by Greenstein. Based on the research results, it is known that the results of hypothesis testing with the ANACOVA test show that there are significant differences in communication skills between students who are taught with the Google Workspace-based Problem Based Learning (PBL) learning model compared to the regular learning model.